Sistema de innovación tecnológica para la mejora de la gestión empresarial en hoteles de 3 estrellas de la ciudad de Babahoyo - Prieto Izquierdo, Katherine (2022)
The post-pandemic situation greatly affected the tourism sector, there are cantons that are still struggling to get ahead and are looking to technological innovation for a possible solution to their problems. In this context, two three-star hotels have been selected in the city of Babahoyo, with the purpose of evaluating them in this regard. For which a management methodological design will be proposed for technological innovation in hotels in the city of Babahoyo. For this, a methodology was proposed that includes a non-experimental design of an exploratory-descriptive type. The methods were used: analytical-synthetic and structural systemic mainly. For the design of the methodology, a bibliographical review of antecedents related to the theme was started, focused mainly on the hotel context. For the collection of information in the context of the study, a diagnostic study was carried out with the application of an observation guide and interviews with several hotel managers in the city of Babahoyo. The proposal included three stages, beginning with a technological and innovation diagnosis of the hotel plant in the city of Babahoyo. The second stage took into consideration the definition of the bases, dimensions and main components associated with technological innovation in hotels. The third stage focused on the presentation of innovation strategies in establishments. With this design, a guide or reference was obtained that guides the work in the management of the innovation and technology components in the hotels of the city of Babahoyo.